Evaluasi Pengendalian Intern Pengeluaran Kas Koperasi Peternakan Bandung Selatan - Annisya Nurul Ashila; Iyeh Supriatna; Rendra Trisyanto Surya; Yanti Rufaedah (Indonesian Accounting Literacy Journal, 2023)
This study was conducted to evaluate the internal control system for cash disbursements at KPBS Pangalengan and to determine the suitability of the cash disbursement system at KPBS Pangalengan with the COSO. In this study, the author uses a descriptive analysis method where the initial stage is to collect data through interviews, questionnaires and documentation, then analyze the data and produce an improvement solution for internal control. The data used are subject and documentary data. From this research, the authors get the results that the internal control system for cash disbursements at KPBS Pangalengan that are not appropriate, such as the unification of the recording function and cash holders.